Respostas estratégicas às pressões institucionais para a sustentabilidade e a sua relação com o grau de internacionalização - Santos, Marindia Brachak dos (2015)
Contemporaneous organizations, inserted in a dynamic environment and with constant changes, need to keep up to date, answering strategically to institutional pressure from government, clients, public organs, society and their institutionalization sector to sustainable practices and the achievement of new markets. The objective of this study is to analyze how strategic answers to institutional pressure for sustainability interact with the level of internationalization in companies from furniture industry sector in RS. To do so, the research has been done in two parts. The first part consisted in an exploratory research with qualitative approach, which has been done by explanatory interviews with three companies from furniture industry sector from RS. The qualitative data has been analyzed using techniques of content analysis. In the second part, a descriptive and quantitative approach has been done by the use of a survey. A questionnaire was developed based on the qualitative results and the literature about the theme. The quantitative data has been analyzed by univariated, bivariated and multivariated statistics techniques. The conceptual research model is based on two constructs. To identify the strategic answers to institutional pressure to sustainability, the model of Oliver (1991) has been used, and the level of internationalization was evaluated based on the indicators from Floriani (2010). The results show a different behavior in strategic answer in each part. While most of quantitative step s respondents had acquiescence answers, the answers in qualitative part show that they take more active decisions, such us compromise and escape. This result is similar to the one found in the literature which states that companies answer in a different way due to institutional pressure. In relation to internationalization level, it can be noted that the percentage of returns to sells in internationalization activities is still low. This result could be related to the choice of input model, which is generally the exportation. This input strategy in international markets offers less risk, and demands less investment, such us executives in exterior. Furthermore, companies indicate that, in countries with international transactions, the demand in sustainable terms is not a decisive criteria for business. This way, it has been possible to see that the companies investigated have a low level of internationalization. In relation to correlated factors, it has been seen that the commitment is associated, although in low level, to the way companies enter in exterior. This association suggests that, as companies choose for different levels of input in international market, the compromising of these companies with new countries arises. So, strategic answers to institutional pressure for sustainability relate with the level of internationalization, anyway, this association is still low and moderate.